A novel high dextran yielding Weissella cibaria JAG8 for cereal food application. (May 2013) - Rao, T. Jagan Mohan; Goyal, Arun
<x xml:space="preserve">Abstract</x> A new isolate from apple (Malus domestica) producing dextransucrase and dextran was characterized by morphological, biochemical and 16S rDNA analyses. The bacterium that was identified as Weissella cibaria (GenBank accession number KC110687) was Gram positive, non-motile, short rod, catalase negative, vancomycin resistant. The maximum dextransucrase activity (5.8 U/ml) as well as dextran concentration of 38 mg/ml was observed at 24°C after 12 h of growth under static condition. The polyethylene glycol (PEG)-400 fractionation of partially purified enzyme showed a specific activity of 20.0 U/mg and displayed a single homogenous band of molecular size 177 kDa on sodium dodecyl sulphate-Poly acrylamide gel electrophoresis (SDS-PAGE) (7.5%). The dextran was enzymatically synthesized using dextransucrase and substrate sucrose. Dextran was purified by alcohol precipitation for further characterization. The rheological analysis of dextran elucidated a non-Newtonian pseudoplastic behaviour. 1H and 13C NMR analyses revealed the fact that the dextran contained d-glucose monomer with 93.0% of α(1 → 6) linear and 7.0% of α(1 → 3) branched linkages.